Bumbling bureaucrats, sluggish courts and forum-shopping elites - Mwangi, E. (2010)
For close to two decades Maasai herders in Southwestern Kenyan have been struggling to subdivide their collectively held group ranches into individually owned and titled parcels. Scholars have indicated that conflicts over property assignment are resolved where more powerful individuals can either bear the costs of extended conflict or can credibly threaten retaliation. The conditions under which conflicts persist are less well understood, yet persistent, non-violent conflicts can have significant impacts on livelihoods and land management. Based on in-depth interviews and reviews of archival material, this case study provides an account of the persistence of distributional conflict during the subdivision of the Maasai group ranches. The study suggests that fragmented, uncoordinated authority renders conflict resolution difficult where asymmetries of power and resources among competing actors are minor and where political entrepreneurs perceive opportunities for vote seeking. Such conditions, which allow forum-shopping among competing actors, contribute to the conflict’s persistence